Comments on Dante’s Conception of Value - Barcsi, Tamás (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
Dante Alighieri (1265–1321) is arguably one of the greatest figures in Western culture. A separate discipline, Dantist Studies, is concerned with exploring the different layers of his art. Without wishing to place myself among the scholars of this discipline, I would like to offer a few thoughts, mainly of an ethical nature, on the relationship of Dante’s works to the Renaissance.